DETERMINANTS OF SALES VOLUME OF HEALTH SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2019-2023 PERIOD - Hafif, Alimul; Wartoyo, Wartoyo; Widagdo, Ridwan (Faculty of Economics and Business, 2025)
The purpose of this study is to measure the influence of production costs, selling costs, and general administrative costs on sales volume in health sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period either partially or simultaneously. The method used is a quantitative method with panel data from secondary data sources and analyzed using panel data regression with Common Effect, Fixed Effect, and Random Effect testing models. The sample and population are sourced from Health Companies listed on the IDX for the 2019-2023 period. The population used is 34 companies with a sample of 9 companies. Then for data analysis techniques, it starts with a panel data selection test, a classical assumption test, and a hypothesis test. Then the results obtained are (1) Production costs affect sales volume. (2) The cost of sales has no effect on the volume. (3) General administrative costs affect sales volume. (4) Simultaneously production costs, selling costs, and general administrative costs affect sales volume. Then an adjusted R-square value of 99.59% was also obtained.